1990
DOI: 10.1161/01.atv.10.6.1032
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood impedance platelet aggregometry and ischemic heart disease. The Caerphilly Collaborative Heart Disease Study.

Abstract: The Caerphilly Collaborative Heart Disease Study is based on a large cohort of men who were ages 49 to 64 years at the time of the study. We report the results for platelet aggregation measured in whole blood from a subsample of 308 men. The index of sensitivity used was the minimum concentration of adenosine diphosphate that produced a defined degree of impedance change in the Chronolog 560 aggregometer. There was a marked association between aggregation and prevalent ischemic heart disease (IHD). The odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 25 publications
(13 reference statements)
0
36
0
Order By: Relevance
“…The Caerphilly Collaborative Heart Study recruited a general population of 2,398 men aged between 49 and 66 years in 1979 to 1982 (78)(79)(80)(81)(82). The risk of CHD and the association with platelet aggregation measurements was assessed.…”
Section: Platelets As Predictors Of Vascular Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Caerphilly Collaborative Heart Study recruited a general population of 2,398 men aged between 49 and 66 years in 1979 to 1982 (78)(79)(80)(81)(82). The risk of CHD and the association with platelet aggregation measurements was assessed.…”
Section: Platelets As Predictors Of Vascular Eventsmentioning
confidence: 99%
“…However, aggregometry procedures in PRP may provide a cheaper and quicker tool to estimate cardiovascular risk, while impedance changes in whole blood are slower, have poor reproducibility, and their cost is higher because of the use of the platinum electrodes that may need replacement. 11,16,19,27,28,48,50,58,[78][79][80][81][82]131,132 Aggregometry procedures in subpopulations of the Caerphilly prospective study performed in PRP and whole blood failed to prove that increased platelet hyperactivity is significantly related to an increased risk of subsequent CHD (78)(79)(80)(81)(82). However, there is evidence of such a link from some other studies (83).…”
Section: Aggregometry Proceduresmentioning
confidence: 99%
“…No relations were reported with angina. Platelet aggregation carried out in WB in a sub sample of 308 men, showed that there was a marked association with prevalent CHD [70]. Significant relations were shown between past MI and electrocardiographic evidence of ischaemia and ADP-induced aggregation and between electrocardiographic evidence of thrombin-induced aggregation [71].…”
Section: Epidemiological Studies In Healthy Popula-tionsmentioning
confidence: 95%
“…The Caerphilly Collaborative Heart Disease Study was carried out in a large cohort of men (2,398) aged 49-66 years [69][70][71][72][73][74]. Agonist-induced platelet aggregation was assessed in fasting blood samples in relation to prevalent angina, past MI and electrocardiographic evidence of CHD.…”
Section: Epidemiological Studies In Healthy Popula-tionsmentioning
confidence: 99%
“…The Caerphilly Collaborative Heart Study measured platelet aggregation and noted it to be a significant risk factor for ischemic heart disease even after controlling for other risk factors [12]. The HAPARG study showed that spontaneous platelet aggregation was a risk factor for vascular occlusive events [13].…”
Section: Platelet Aggregometrymentioning
confidence: 99%